Prácticas de autocuidado y religiosidad en la pandemia COVID 19 en padres de familia de la institución educativa pública nivel primaria N° 60201 Orán Bajo Amazonas, Maynas 2021 - Diaz Iglesias, Deicy (2022)
The research was raised as a question: How are the practices of self-care and religiosity in the covid 19 pandemic in parents of the public educational institution primary level N ° 60201 located in Orán Bajo Amazonas, province of Maynas in the year 2021? And as the main objective to describe the practices of self-care and religiosity during the covid 19 pandemic in the parents of the nominated educational institution. The methodology used has been a cross-sectional, field design, attending only to a single variable and the type of research was descriptive. The 110 parents of the educational institution have been the population and sample of the study. The survey technique was used to obtain the data and a questionnaire was used as an instrument, which was previously validated by experts. The most important conclusion of the study is that self-care and religiosity practices in the COVID 19 pandemic in parents of the educational Institution show a good level in 59.1% of them and a very good level in 40.9%. These findings also confirm that there are no parents at a fair or poor level.